2020
DOI: 10.1080/23802359.2020.1730728
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Riccia fluitans L. (Ricciaceae, Marchantiophyta): investigation of intraspecific variations on mitochondrial genomes of R. fluitans

Abstract: Riccia fluitans L. is the most common species in Riccia genus. To investigate intraspecific variations on mitochondrial genomes of R. fluitans, we completed mitochondrial genome of R. fluitans. Its length is 185,640 bp, longer than that of NC_043906 by 19 bp and it contains 74 genes (42 protein-coding genes, 3 rRNAs, 28 tRNAs, and 1 pseudogene). 18 single nucleotide polymorphisms (SNPs) and 19 insertions and deletions are identified, higher than that of Marchantia polymorpha subsp. ruderalis. One non-synonymou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…It contains 73 genes (41 protein-coding genes, 3 rRNAs, 28 tRNAs, and 1 pseudogene) and overall GC content is 42.9%. Nad7 gene was revealed as pseudogene in both W. denudata mitochondrial genomes which is similar to the other Marchantiales species (Dong et al 2019;Kwon et al 2019aKwon et al , 2019bMin et al 2020).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…It contains 73 genes (41 protein-coding genes, 3 rRNAs, 28 tRNAs, and 1 pseudogene) and overall GC content is 42.9%. Nad7 gene was revealed as pseudogene in both W. denudata mitochondrial genomes which is similar to the other Marchantiales species (Dong et al 2019;Kwon et al 2019aKwon et al , 2019bMin et al 2020).…”
supporting
confidence: 56%
“… 2019b ), Riccia fluitans (18 SNPs; 0.0097% and 19 INDELs; 0.010%; Min et al. 2020 ), Dumortiera hirsuta (12 SNPs; 0.0067% and 24 INDELs; 0.013%; Dong et al. 2019 ; Kwon et al.…”
mentioning
confidence: 99%
“…In addition, Crandall-Stotler et al reported that chloroplast gene of W. denudata was aligned with those of Riccaceae (Crandall-Stotler et al 2009), displaying incongruent with the phylogenetic trees (Figure 1). This incongruencies was not reported from those mitochondrial genome analyses (Kwon et al 2019c(Kwon et al , 2019dMin et al 2020). Taken together, additional studies for understanding these incongruencies are strongly required in near future.…”
mentioning
confidence: 74%
“… 2019c , 2019d ; Min et al. 2020 ). Taken together, additional studies for understanding these incongruencies are strongly required in near future.…”
mentioning
confidence: 99%
“…), Riccia fluitans(Min et al 2020), and Monosolenium tenerum(Dong et al 2019). However, additional investigations are required because some of intraspecific variations on mitochondrial genomes, including Liriodendron tulifipera(Park et al 2019) and Arabidopsis thaliana (Park et al in preparation) display larger numbers.…”
mentioning
confidence: 99%